A bibliometric analysis of sentinel lymph node biopsy in melanoma of the top 90 cited publications - Zhen Yu Wong; Aisha Chaudry; Samuel Teklay; Zhen Ning Wong; Oluwatobi Adegboye; Pojsakorn Danpanichkul; Ryan Faderani; Muholan Kanapathy; Afshin Mosahebi (Melanoma Management)
Background This bibliometric analysis aims to describe research trends and assess the methodological quality of the highest-impact SLNB research in melanoma.Methods We identified the 90 most cited publications on SLNB in melanoma using Web of Science, covering all available journal years (from 2005 to date). The Oxford Center for Evidence-Based Medicine (OCEBM) Levels of Evidence (LOE) were used to assess the methodological quality of each study.Results The 90 most cited publications on SLNB in melanoma collectively garnered 10,314 citations. Citation counts per publication ranged from 44 to 1,405 (mean 114.6 ± 185.2), with the highest-cited study authored by Professor Donald Morton et al. The majority of publications was classified as LOE 3 (n = 36). The United States of America (USA) led in publication output with 43 articles. Professors Merrick Ross (USA) and John Thompson (Australia) were the leading authors by publication count. The University of Sydney (Australia), University of Texas System, and Anderson Cancer Center (USA) were the top contributing institutions. Annals of Surgical Oncology published most articles.Conclusions This bibliometric analysis provides a comprehensive overview and valuable reference for future researchers in the field of SLNB in melanoma.